2021
DOI: 10.1136/bmjgh-2021-006951
|View full text |Cite
|
Sign up to set email alerts
|

‘Learn from the lessons and don’t forget them’: identifying transferable lessons for COVID-19 from meningitis A, yellow fever and Ebola virus disease vaccination campaigns

Abstract: IntroductionCOVID-19 vaccines are now being distributed to low- and middle-income countries (LMICs), with global urgency surrounding national vaccination plans. LMICs have significant experience implementing vaccination campaigns to respond to epidemic threats but are often hindered by chronic health system challenges. We sought to identify transferable lessons for COVID-19 vaccination from the rollout of three vaccines that targeted adult groups in Africa and South America: MenAfriVac (meningitis A); 17D (yel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Hepatitis B immunization is recommended for all adults, including HCWs [ 48 ]; we, therefore, used hepatitis B vaccination status as a marker for compliance with required routine vaccinations. Ebola vaccination status was tested as a surrogate for HCWs’ attitudes towards novel or emerging communicable diseases, given the recent history of an Ebola epidemic in the country [ 49 ]. We found that although there was a trend towards lower COVID-19 vaccine hesitancy among HCWs who had previously received the hepatitis B or Ebola vaccines, this association did not attain statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B immunization is recommended for all adults, including HCWs [ 48 ]; we, therefore, used hepatitis B vaccination status as a marker for compliance with required routine vaccinations. Ebola vaccination status was tested as a surrogate for HCWs’ attitudes towards novel or emerging communicable diseases, given the recent history of an Ebola epidemic in the country [ 49 ]. We found that although there was a trend towards lower COVID-19 vaccine hesitancy among HCWs who had previously received the hepatitis B or Ebola vaccines, this association did not attain statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, its implementation has not always been effective, 19 even though lessons learnt from previous vaccination programmes show that community engagement is an effective and essential tool. 20 In South Asia, for example, community engagement efforts in Ebola and Polio vaccines were used consistently and successfully. 21 A recent review on community engagement for the prevention and control of infectious diseases 19 noted how community engagement has been used to support vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Community engagement has been part of global recommendations and guidelines on the response to the COVID-19 pandemic. However, its implementation has not always been effective,19 even though lessons learnt from previous vaccination programmes show that community engagement is an effective and essential tool 20. In South Asia, for example, community engagement efforts in Ebola and Polio vaccines were used consistently and successfully 21.…”
Section: Introductionmentioning
confidence: 99%
“…The opioid epidemic (Fortunato & Gigliotti, 2019 ), and viral outbreaks throughout the world (Ebola, SARS, etc. ), exemplify healthcare crises with no easily defined cause or agent of responsibility (Collins et al, 2021 ). Unique in terms of its global spread, contagiousness, and high mortality rate, in combination with inundated healthcare systems, COVID‐19 is a historic example of a prolonged crisis with shifting sources of blame and responsibility.…”
Section: Literature Reviewmentioning
confidence: 99%